Synthesis of nanogate structure in GO-ZnS sandwich material - Kumar, Praveen; Luwang, Meitram Niraj (Scientific Reports, 2019)
Graphite Oxide (multi-layer) composite with other materials has a huge application in various field of science, due to its excellent and unique properties. Even though from past decade, immense research has been done by materials scientists in this field, but the chemistry is still not yet satisfactory. Here, in this work, through the discovery of Nanogate structure, we have reported for the first time the experimental results that enlightened the clear chemistry between the GO and ZnS which is further supported by the DFT calculations. This novel synthesis method led to the discovery of nanogate structure sandwiched between the GO layers. The nanogate formation also shows enhanced properties for various applications like photocatalytic activities, etc. Due to the nanogate formation, there might be a possibility of enormous generation of electrons on excitation of the composite materials, which can be a boom for various applications like photocatalysis, water splitting, solar cell, etc.